Development, Synthesis and Characterization of Biomimetic Model Complexes - Brandes, Elizabeth; Sahr, Kristin; Schuelke, Ariel (My University, 2014)
This project involves the development, synthesis and characterization of new bioinorganic model complexes that mimic the active site of a biologically relevant dioxygenase enzyme, Quercetin Dioxygenase (QDO). The goal of this research is to understand how the unique active site of this enzyme cleaves the O-heteroatomic ring of quercetin by evaluating the functionality of a series of metal complexes with ligand systems similar in structure to the active site of QDO.
Color poster with text, charts, and models.
Keywords: Metalloenzymes; Quercetin dioxygenase (QDO); Biomimetic model complexes; Posters